“Recovery” from the diagnosis of autism – and then? - Barnevik Olsson M (Dove Medical Press, 2015)
Martina Barnevik Olsson,1,2 Joakim Westerlund,1,3 Sebastian Lundström,1 MaiBritt Giacobini,2,4 Elisabeth Fernell,1,5 Christopher Gillberg1 1Gillberg Neuropsychiatry Centre, Institution of Neuroscience and Physiology, Sahlgrenska Academy, Gothenburg University, Gothenburg, Sweden; 2PRIMA Child and Adult Psychiatry, Stockholm, Sweden; 3Department of Psychology, Stockholm University, Stockholm, Sweden; 4Department of Molecular Medicine and Surgery, Karolinska Institutet, Stockholm, Sweden; 5Research and Development Centre, Skaraborg’s Hospital, Skövde, Sweden Background: The aim of this study was to follow up the 17 children, from a total group of 208 children with autism spectrum disorder (ASD), who “recovered from autism”. They had been clinically diagnosed with ASD at or under the age of 4 years. For 2 years thereafter they received intervention based on applied behavior analysis. These 17 children were all of average or borderline intellectual functioning. On the 2-year follow-up assessment, they no longer met criteria for ASD.Methods: At about 10 years of age they were targeted for a new follow-up. Parents were given a semistructured interview regarding the child’s daily functioning, school situation, and need of support, and were interviewed using the Vineland Adaptive Behavior Scales (VABS) and the Autism – Tics, Attention-deficit/hyperactivity disorder (AD/HD), and other Comorbidities (A-TAC) telephone interview.Results: The vast majority of the children had moderate-to-severe problems with attention/activity regulation, speech and language, behavior, and/or social interaction. A majority of the children had declined in their VABS scores. Most of the 14 children whose parents were A-TAC-interviewed had problems within many behavioral A-TAC domains, and four (29%) had symptom levels corresponding to a clinical diagnosis of ASD, AD/HD, or both. Another seven children (50%) had pronounced subthreshold indicators of ASD, AD/HD, or both.Conclusion: Children diagnosed at 2–4 years of age as suffering from ASD and who, after appropriate intervention for 2 years, no longer met diagnostic criteria for the disorder, clearly needed to be followed up longer. About 3–4 years later, they still had major problems diagnosable under the umbrella term of ESSENCE (Early Symptomatic Syndromes Eliciting Neurodevelopmental Clinical Examinations). They continued to be in need of support, educationally, from a neurodevelopmental and a medical point of view. According to parent interview data, a substantial minority of these children again met diagnostic criteria for ASD. Keywords: autism spectrum disorder, autistic traits, AD/HD, A-TAC, Vineland, cure